Novejša slovenska ljubezenska poezija in njen evropski kontekst - Pavlič, Darja (Slavistična revija, 2006)
The article deals with the topis of love in the poetry of two contemporary Slovene poets, Milan Jeaih and Boris A. Novak, by examining the connection between their work and the European literary tradition. Literary criticism did not develop a genre definition on the basis of countless poems about love, which would standardize various hostorical views of love and precisely define the content of love poetry. As a point departure for the treatment of the two poets, the first part of the article presents Rougemont's concept of passionate love, derived from the myth of Tristan and Isolde.
Keywords: Jesih, Milan; literarna tradicija; literary tradition; ljubezen; ljubezenska poezija; love; love poetry; mit o Tristanu in Izoldi; myth of Tristan and Isolde; Novak, Boris A.; Slovene literature; Slovene poetry; slovenska knjiženost; slovenska poezija; tematologija